Creating the Applied Subject Area Ontology by Means of the Content of the Digital Semantic Library - Ataeva, O. M.; Serebryakov, V. A.; Tuchkova, N. P. (Lobachevskii journal of mathematics, 2022)
This article is devoted to the problem of including a subject area in a semantic library. The subject area is considered, which was not previously presented in part of the ontology of the digital library. A method based on the technology of establishing semantic links with the already accumulated content of the library is proposed. Main idea of the inclusion method is to use dictionaries, thesauri and links to the mathematical encyclopedia. They are used to attach a new scientific publication metadata set to an existing library metadata set. In the course of preliminary processing of texts of scientific publications, their semantic analysis is carried out and a local description of the subject area of this array is formed within the content of the library. Such subject areas as ordinary differential equations, partial differential equations, equations of continuum mechanics, equations of composite mechanics and their solutions expressed in terms of special functions of mathematical physics are considered. The description of the mathematical encyclopedia in its classical form is the central resource. It allows us to identify the appropriate classifiers through the links of the equations of applied problems and their solutions and use them also to form a description of the subject area. This subject area is new and has not been described in our digital library before. Proposed procedure is made possible only by data integration in the library. This takes into account the expansion of the description of subject areas related to the applications of mathematics in interdisciplinary research and technology. The implementation of this procedure is one of the new directions for filling the semantic libraries. It uses the approach of data integration and saturation with connections that are revealed only in the process of analyzing new data. If new references are found in the library during the process of adding a new description, then this method will also make it possible to identify and fill in the gaps in the description of related areas of mathematics, such as applications of solutions to classical problems of mathematical physics.